Development of student sport in agrarian universities of Russia at the present stage - Markin, E.V.; Nikiforova, O.N.; Soparev, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the main trends in the development of student sport in agrarian universities of Russia. Methods and structure of the study. The methodological basis of the study consisted of the analysis and synthesis of documents regulating the development of student sport in recent years. The materials of speeches by heads and representatives of ministries and departments, as well as famous athletes at events of various levels, were analysed. Announcements, news and final publications on the websites of ‘Rosstudsport,’ RSSS, ASSK Russia and other social networks were analysed. Results and conclusions. The main trends in the development of student sport in agrarian universities until 2030 will be: the introduction of a mandatory set of competitions in key sports included in the AgroLeagues; the inclusion of agrarian universities in the projects of the RSSS and ASSK Russia; the creation of student sports clubs in 100% of universities; the creation of a long-term plan for the sporting life of students until 2030; partnerships with local agro-industrial complexes for participation in events outside universities, ambassadorship for organisations and enterprises; the formation of a community of agro-industrial complex and student sport leaders; the use of digital technologies for organising events in the media space and social networks; the search for sources of financing, and others. As the main mechanism for developing student sport, it is proposed to create AgroLeagues within the structure of universities and to hold the All-Russian Spartakiad ‘AgroLeague’ in 10 sports in several stages.